Report of Sub-Committee on Strengthening M and E Systems in Social Sector Development Ministries - Planning Commission (Planning Commission, 2007)
"Monitoring and evaluation are essential tools adopted in programme management for bringing about transparency, accountability, efficiency and good governance. While monitoring attempts to ensure that the intended inputs are going in right direction (in right quantity, in right quality and at right place) for their transformation into intended activities and outputs of the programme, evaluation makes an assessment/examination of the implementation processes and the impact of the programme on the intended target groups. Monitoring Outcomes instead of Outlays The approach paper on 11th Five Year Plan has highlighted the issues underlying the subject of monitoring and evaluation which are presented below. Monitoring and evaluation of government programmes is crucial to learn lessons about the design and implementation of programmes which can help increase their effectiveness. Traditionally, plan monitoring has been done by tracking expenditure levels achieved in relation to outlays. While this is a measure of the pace of implementation, it is not a measure of effectiveness."
"Planning Commission Programme Evaluation Organisation Govt, Of India New Delhi"